2012
DOI: 10.1159/000341148
|View full text |Cite
|
Sign up to set email alerts
|

Septo-Optic Dysplasia: Antenatal Risk Factors and Clinical Features in a Regional Study

Abstract: Background: Septo-optic dysplasia (SOD) is a disorder with postulated environmental and genetic aetiology. This study delineates clinical features and potential perinatal environmental factors along with epidemiology in SOD children. Methods: Assessment of patients with SOD triad features in the UK West Midlands region. Results: Of 227 patients identified between 1998 and 2009 with 1 or more feature of the triad, 55 had midline defects, 149 had optic nerve hypoplasia and 132 had hypopituitarism. Eighty-eight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…This is presumably related to SOD. The most common hormone deficiency is GH alone or in combination with deficiencies in other pituitary hormones [1][2][3][4]. Secondary adrenal insufficiency due to ACTH deficiency has also been reported in SOD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is presumably related to SOD. The most common hormone deficiency is GH alone or in combination with deficiencies in other pituitary hormones [1][2][3][4]. Secondary adrenal insufficiency due to ACTH deficiency has also been reported in SOD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that the degree of ACTH deficiency can gradually progress in congenital combined pituitary hormone deficiency [5]. Moreover, Atapattu et al [4] reported that among 227 patients with SOD, 3 patients died from adrenal crisis. Therefore, the evaluation of the hypothalamic-pituitary-adrenal system is mandatory in patients with SOD.…”
Section: Discussionmentioning
confidence: 99%
“…Some antenatal risk factors such as younger maternal and paternal age, primigravida birth, drug and alcohol abuse, maternal diabetes and first trimester bleeding have been associated with SOD 16 17. The association of SOD and increased first trimester bleeding may indicate that SOD is a vascular disruption sequence 17…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen years later, the clinical signs observed in SOD were defined as De Morsier syndrome. In 1970, hypophyseal dysfunction was shown in patients with SOD (2). The incidence of this disease, which is equally seen in both sexes, is 1/10 000 (2,3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In 1970, hypophyseal dysfunction was shown in patients with SOD (2). The incidence of this disease, which is equally seen in both sexes, is 1/10 000 (2,3,4). Diagnosis is made by the presence of two out of three criteria, namely, optic nerve hypoplasia, hypopituitarism and midline brain defects (septum pellucidum and/or corpus callosum agenesis/hypoplasia) (2,3,4,5).…”
Section: Introductionmentioning
confidence: 99%